Legal Terminology in African Languages - Alberts, Mariëtta (Lexikos, 1997)
This article deals with the project on legal terminology in the African languages. It focuses on terminology aspects relating to the coining of terms for the legal profession. Terminology development in South Africa has been hampered by a number of sociolinguistic factors. During recent years South Africa has seen considerable changes regarding the function of the indigenous languages, and this situation gave rise to an urgent need for terminology in various subject fields and knowledge domains. A demand arose for legal terminology in African languages. This need for legal terminology gave rise to the establishment of the Centre for Legal Terminology in African Languages. The aim of the Centre is to make legal terminology more accessible to the local indigenous population. The background of the legal terminology project is given and the various principles on which the working procedure is based, are discussed. Various aspects regarding the present project (such as financing, time-schedule, training and terminological problems encountered) are treated.